Status gizi, densitas zat gizi, dan keragaman pangan anak balita selama pandemi COVID-19 di Kabupatan Bangli, Bali - Kadek Tresna Adhi; Ni Putu Widarini; Ni Luh Putu Suariyani; Iwan Abdi Suandana; Pande Putu Januraga (Jurnal Gizi Klinik Indonesia, 2022)
Nutritional status, nutrient density, and dietary diversity of children under five during the COVID-19 pandemic in Bangli Regency, Bali